Correlation between Mandibular 2nd Molar Calcification Stages and CVMI among Southern Punjab Population - Umal Asim, Zubair Hassan Awaisi, Zubair Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out whether a correlation exists among the CVMI and dental calcification stages. Study design: Case-control study Place and duration of study: Department of Orthodontics, Nishtar Institute of Dentistry, Multan from 1st October 2020 to 30th April 2021 Methodology: One hundred and fifty orthopantomograms and lateral cephalograms patients were incorporated. The dental maturity was evaluated using8 stages of Demirjian index from stage A to H. This index is graded by determining the calcification stages of the left mandibular second molar tooth on an orthopantomogram. The CVM stages based on the morphology of 2nd, 3rd and 4th cervical vertebral bones on a lateral cephalogram, discern the skeletal maturity. This included 6 stages from stage 1 to 6, based on the depth of concavity and shapes of the vertebrae. Results: The results showed a significant correlation amongst the dental calcification stages and CVMI, having a Pearson’s correlation coefficient ‘r’ of 0.741. A gender dimorphism was observed with males showing more progressive dental calcification stages in the CVM stages 2 and 3 as compared to their female counterparts. The dental calcification stage ‘D’ correlates with CVM stage 1 which occurs approximately 2 years prior to adolescent growth spurt. CVM stage 3 i.e. peak of adolescent growth spurt conforms to dental calcification stage ‘F’ in females and stage ‘G’ in males. The dental calcification stage ‘H’ correlated with CVM stages 5 and 6 which indicate the cessation of growth. Conclusion: The lower second molar tooth calcification stages are a valid measure of skeletal age and can be effectively utilized to estimate patient’s age in orthodontic practice. Keywords: Cervical vertebral maturation, Dental calcification, Mandibular 2nd molar, Skeletal maturity